Structural Model of the Impact of Talent Management on Human Resource Productivity and Innovation in the National Road Maintenance and Transportation Organization - Koushki, Masoud; Taghizadeh, Houshang; Pourmahmoud, Jafar (Management Strategies and Engineering Sciences, 2025)
The present study aimed to examine the impact of talent management dimensions on human resource productivity and innovation in the National Road Maintenance and Transportation Organization. This research is a descriptive-survey study with an applied purpose. The statistical population included all employees of the National Road Maintenance and Transportation Organization. Given the limited size of the population, the sample size was considered equal to the statistical population (N = 64). After establishing the validity and reliability of the measurement tools, the standardized Armstrong Talent Management Questionnaire (2006), the Human Resource Productivity Scale, and the Patchen Job Innovation and Creativity Scale (1965) were used for data collection. Data analysis was conducted using descriptive and inferential statistics as well as structural equation modeling (SEM). The research results indicated that talent management and its dimensions significantly influence human resource productivity and innovation in the National Road Maintenance and Transportation Organization. In the total effect analysis, talent management had the highest impact on human resource productivity (β = 0.92). The coefficient of determination (R²) for the endogenous variables demonstrated that 29% and 91% of the variance in human resource productivity and innovation, respectively, could be explained by the exogenous variables. Based on the findings of this study, proper implementation of talent management and its dimensions can enhance human resource productivity and, consequently, improve innovation within the National Road Maintenance and Transportation Organization. This, in turn, increases the efficiency of talented individuals in the organization.